Cultural Importance Of Useful Plants In Kenduri Sko Traditional Ceremony Of Kerinci Community, Hamparan Rawang Sub-District, Sungai Penuh City, Jambi Province - Adriadi, Ade; Asra, Revis; Wahyuni, Fitra; Marsanda, Firda Dwi; Hikmah , Nurul (Berita Biologi, 2025)
Hamparan Rawang District is one of the sub-districts in Sungai Penuh City, Jambi Province which has a culture and tradition. One of the traditional ceremonies in Hamparan Rawang District is the Kenduri Sko Traditional Ceremony or what is called Kenduri Pusako. Assessment of the cultural importance of plant species diversity in Kenduri Sko is useful in ethnobotanical studies which include subsistence activity strategies and traditional classifications. Data collection was carried out by interviewing key informants using the "in depth interview" method, then estimating the cultural importance value of each plant species used in Kenduri Sko with the ICS(Index Cultural Significance) formula. The results of the study found that Kenduri Sko is a tradition that symbolises the greatness of customs in their respective regions with the aim of improving friendship and which is characterised by the crowning of traditional titles, cleaning heirlooms and uniting male children of butino children. Based on the results of interviews and estimation of ICS values, it is known that the ICS value of useful plants for Kenduri Sko ranges from 8 to 50. Areca nut (Areca catechu L ) has the highest ICS value, while Cynodon dactylon (L.) Pers. has the lowest ICS value.